Keefektifan konseling kognitif behavioral dengan teknik restrukturisasi kognitif untuk meningkatkan endurance siswa - Khuzaimatul Jannah; Kadek Suranata; Ni Ketut Suarni (Psychocentrum Review, 2019)
This study aims to determine the effectiveness of cognitive behavioral counseling with cognitive restructuring techniques to improve endurance of 1st grade students at SMA Negeri 4 Singaraja. This experimental study used the Pretest Posttest Control Group Design. The study population was students of 1st grade SMA Negeri 4 Singaraja. The research sample consisted of 54 students. Through random sampling, 23 students were placed in the experimental group and 31 students were the control group. Data collection in this study used a questionnaire. The data in this study were analyzed by independent samples t-test using JASP Version 0.7.5.5 and d’Cohen for calculate level of effectiveness. The results t = 8.577 with p= 0.001, then p <0.05. Effect Size (ES) testing shows a high level of effectiveness (ES = 2.361). These results prove that cognitive behavioral counseling with cognitive restructuring techniques is effective for improving the endurance of 1st grade students at SMA Negeri 4 Singaraja.